Computational Mesomechanics of Surface-Modified Titanium; AIP Conference Proceedings; Vol. 1783 : Advanced Materials with Hierarchical Structure for New Technologies and Reliable Structures 2016 - Balokhonov R. R. Ruslan Revovich; Martynov S. A.; Romanova V. A.; Panin A. V. Alexey Viktorovich; Kazachenok M. S.; Batukhtina E. E.; Shakhijanov V. S. (2016, 2016)
Title screen